Radial scars and subsequent breast cancer risk: a meta-analysis. - Mengmeng Lv; Xingya Zhu; Shanliang Zhong; Weixian Chen; Qing Hu; Tengfei Ma; Jun Zhang; Xiaohui Zhang; Jinhai Tang; Jianhua Zhao (PLoS ONE, 2014)
The relationship between radial scars and breast cancer is unclear, as the results of different studies are inconsistent. We aim to solve the controversy and assess the breast cancer risk of radial scars.Case-control or cohort studies about radial scars and breast cancer risk published in PubMed, Web of Science and the Cochrane Library from 2000 to 2013 were searched. Heterogeneity for the eligible data was assessed and a pooled odds ratio (OR) with 95% confidence interval (CI) was calculated.Five observational studies involving 2521 cases and 20290 controls were included in our study. From pooled analysis, radial scars were found to have a 1.33 fold increased risk of breast cancer, but which was not significant (P = 0.138). Sample size contributed to heterogeneity. In subgroup analysis, the results pooled from studies with sample size >2000 show that presence of radial scars was associated with 1.6 times breast cancer risk compared to absence of radial scars. Radial scars increased the risk of breast cancer among women with proliferative disease without atypia, but no significant association between radial scars and carcinoma was noted among women with atypical hyperplasia.Radial scars tend to be associated with an increased breast cancer risk. Radial scars should be considered among women with proliferative disease without atypia, while atypical hyperplasia is still the primary concern among women with both radial scars and atypical hyperplasia.